Cryopreservation of boar semen - Jovičić, Marija; Chmelíková, Eva; Sedmíková, Markéta (Czech Journal of Animal Science, 2020)
Sperm cryopreservation is the best technology for long-term storage of the semen. However, the damage of boar spermatozoa by cryopreservation is more severe than in other animal species and a standardized freezing protocol for efficient cryopreservation has not been established yet. Semen quality and freezability vary greatly between breeds as well as between individual boars and even the season. Boar spermatozoa are sensitive to low temperatures; they sustain damage and a high rate of mortality and freezing/thawing the boar semen may strongly impair the sperm function and decrease the semen quality. The freezability of boar semen can be influenced by a cryopreservation procedure, and also by using various additives to freezing and thawing extenders such as antioxidants. In order to obtain acceptable results after thawing the boar semen, it is necessary to combine an optimal amount of additives (glycerol, egg yolk, sugars, antioxidants), cooling and warming velocities.
Keywords: additives; antioxidants; extenders; freezability; sperm